Incidental Adreno-Cortical Adenoma, why Surgery? a Case Report - Solís López, Diego R.; Rodríguez Hernández, Zaida N.; Solís López, David H. (Puerto Rico Health Sciences Journal, 2010)
Introduction: Incidental adrenal tumors are commonly benign, but reports demonstrate that if the characteristics of the tumor are not clear, on images surgery is the procedure of choice. Our objective through this case is to show that laparoscopic adrenalectomy is a safe approach for adrenal incidental tumor regardless of radiological findings. Case report: A 52 year-old female with arterial hypertension (HBP), cramps, and back pain at right side, probably related to her chronic back pain history. She went for check up and a left adrenal mass on MRI described as myelolipoma was found incidentally. Laboratories were unremarkable except aldosterone and cortisol levels were slightly elevated. She was treated for hypertension for about a year. The patient underwent to a successful laparoscopic left adrenalectomy, after which the patient blood pressure was stable with out any medications, and the aldosterone and cortisol levels decreased. The pathological report was adrenal cortical adenoma with central hemorrhage and not a myelolipoma as described in images on magnetic resonance imaging (MRI). Conclusion: The use of imaging for diagnosis, clinical management and decision making is very controversial. Laparoscopic surgery for adrenal masses is a safe procedure for tumors of 6 cm regardless of the radiological description.